CAUSES OF FEVER IN ADULTS IN THALL AND SURROUNDING AREAS - Shah, Sajid Ali; ., Javed; Hussain, Altaf; Ali, Safdar; Rashid, Haroon -ur-; Ahmad, Sheraz (Journal of Ayub Medical College Abbottabad, 2015)
Background: The most common symptom for which the patients are admitted in our hospitals is fever. This study was carried out to know the causes of fever based on clinical and laboratory findings. Methods: In this cross sectional study, 865 consecutive male patients with fever of 100ºF and above were included in the study conducted from January 2010 to April 2012. Results: All the patients were male having age between 17 years and 45 years. Out of the 865 patients, 507 (58.61%) came out to be malarial parasite slide positive, 186 (21.50%) patients were malarial parasite slide negative but were having clinical picture of malaria and responded to anti-malarial treatment, 73 (8.44%) patients were of respiratory tract infections, 21 (2.43%) patients were having gastro enteritis, 20 (2.31%) were diagnosed as cases of typhoid fever, 17 (1.97%) were having urinary tract infections, 24 (2.77%) patients were referred to medical specialist and the rest 17 (1.97%) were grouped as others. Conclusion: The most common cause of fever in our study was malaria. Respiratory tract infections are the second most common cause. Keywords: Malaria, urinary tract infections, respiratory tract infections, Chloroquine.